CHINA’S NARRATIVE ON THE GLOBAL SOUTH: LEGACY OF CONFUCIANISM AND SINICIZATION OF MARXISM EXPLAINED - Zhongxing Bai (Western European Studies, 2025)
Positioned at the intersection of reason and reality, the paper examines China’s Global Civilization Initiative as its key narrative on the Global South in contesting the hegemonic discourses of modernity and concomitant unipolar world order. Through a dialectical analysis, the paper argued how political economy architect, where China’s diplomatic rhetoric is embedded, has been constructed through the synchronous inheritance of Confucianism with Sinicization of Marxism. The study, taking a tentative disenchantment stance, highlights the deconstruction and transcendence of entrenched dichotomies that splits modernity and tradition in political kaleidoscope, core and periphery in economic amphitheater, as well as civilization and “barbarism” in cultural panorama throughout the world. This penetrates every facets of China’s narratives on “Global South”. It goes without saying that such an demonstration must be succinct, not only due to the limited space here for analyzing such a complex process, but also because the author did not set out to present a historical account or exhaustive policy analysis
Keywords: Global South; Global Civilization Initiative; Confucianism